2021
DOI: 10.1021/acs.est.0c06275
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation Analysis of an Impulsive System Describing Partial Nitritation and Anammox in a Hybrid Reactor

Abstract: Low-energy nitrogen removal under mainstream conditions is a technology that has received significant attention in recent years as the water industry drives toward long-term sustainability goals. Simultaneous partial nitritation-Anammox (PN/A) is one process that can provide substantial energy reduction and lower sludge yields. Mathematical modeling of the PN/A process offers engineers insights into the operating conditions necessary to maximize its potential. Laureni et al. ( Laureni Laureni Water Res.201914… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The simulation results showed that removing flocculent sludge is an effective strategy for the washout of NOB (Laureni et al 2019). Wade & Wolkowicz (2021) demonstrate that the parameter space of the PN/A model can be partitioned into regions in which the system converges to different fixed points that represent different outcomes. Unfortunately, the simulation results have not been verified by experimental data.…”
Section: Introductionmentioning
confidence: 91%
“…The simulation results showed that removing flocculent sludge is an effective strategy for the washout of NOB (Laureni et al 2019). Wade & Wolkowicz (2021) demonstrate that the parameter space of the PN/A model can be partitioned into regions in which the system converges to different fixed points that represent different outcomes. Unfortunately, the simulation results have not been verified by experimental data.…”
Section: Introductionmentioning
confidence: 91%
“…So far, the influence of DO, 28−30 temperature, 31 FA, 32,33 FNA, 32 and pH 8,34,35 on the AOB and NOB have been evaluated in classic nitrification models to identify operational boundaries of PN. 8,34,35 These conventional models were built based on the aggregated bulk biomass rather than the microbial community and have never considered various acid-tolerant microorganisms that have an important role in acidic PN. Simulation of the dynamics of the microbial community is thus needed for accurate prediction and regulation of the PN process.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical modeling is an important tool to describe the dynamics of the nitrifying microbial community. So far, the influence of DO, temperature, FA, , FNA, and pH ,, on the AOB and NOB have been evaluated in classic nitrification models to identify operational boundaries of PN. ,, These conventional models were built based on the aggregated bulk biomass rather than the microbial community and have never considered various acid-tolerant microorganisms that have an important role in acidic PN. Simulation of the dynamics of the microbial community is thus needed for accurate prediction and regulation of the PN process …”
Section: Introductionmentioning
confidence: 99%